The first twenty years of the European Central Bank: Monetary policy - Philipp Hartmann; Frank Smets (European Central Bank (ECB), 2018)
On 1 June 2018 the ECB celebrated its 20th anniversary. This paper provides a comprehensive view of the ECB's monetary policy over these two decades. The first section provides a chronological account of the macroeconomic and monetary policy developments in the euro area since the adoption of the euro in 1999, going through four cyclical phases "conditioning" ECB monetary policy. We describe the monetary policy decisions from the ECB's perspective and against the background of its evolving monetary policy strategy and framework. We also highlight a number of the key critical issues that were the subject of debate. The second section contains a partial assessment. We first analyze the achievement of the price stability mandate and developments in the ECB's credibility. Next, we investigate the ECB's interest rate decisions through the lens of a simple empirical interest rate reaction function. This is appropriate until the ECB hits the zero-lower bound in 2013. Finally, we present the ECB's framework for thinking about non-standard monetary policy measures and review the evidence on their effectiveness. One of the main themes of the paper is how ECB monetary policy responded to the challenges posed by the European twin crises and the subsequent slow economic recovery, making use of its relatively wide range of instruments, defining new ones where necessary and developing the strategic underpinnings of its policy framework.
Keywords: E52; E31; E32; E42; N14; G01; 330; European Central Bank; monetary policy; European Economic and Monetary Union; euro area economy; inflation; crisis; non-standard measures; zero-lower bound